The Effect of Budget Allocation and Budget Realization on The Performance of The Inspectorate of General Supervision (Itwasum) of The Indonesian National Police (Polri) - Riyadi, Christianto; Cahaya, Yohanes Ferry (Dinasti International Journal of Management Science, 2025)
This study examines the effect of budget allocation and budget realization on the performance of the Inspectorate of General Supervision (Itwasum) of the Indonesian National Police (Polri). The background of this study is the importance of effective budget management in supporting the optimization of supervision tasks within Polri. The objective is to analyze the relationship between budget allocation, budget realization, and Itwasum Polri’s performance. This research employs a quantitative approach using multiple linear regression analysis. Data were collected from financial reports and performance reports of Itwasum Polri over a specific period. The results reveal that budget allocation significantly and positively affects Itwasum Polri’s performance, while budget realization also has a positive impact, albeit with lower significance. In conclusion, well-planned and well-executed budget management contributes to improving Itwasum Polri’s performance.